Effect of liver histopathology on islet cell engraftment in the model mimicking autologous islet cell transplantation. Issue 6 (2nd November 2017) - Desai, Chirag S.; Khan, Khalid M.; Ma, Xiaobo; Li, Henghong; Wang, Juan; Fan, Lijuan; Chen, Guoling; Smith, Jill P.; Cui, Wanxing
ABSTRACT: Background: The inflammatory milieu in the liver as determined by histopathology is different in individual patients undergoing autologous islet cell transplantation. We hypothesized that inflammation related to fatty-liver adversely impacts islet survival. To test this hypothesis, we used a mouse model of fatty-liver to determine the outcome of syngeneic islet transplantation after chemical pancreatectomy. Methods: Mice (C57BL/6) were fed a high-fat-diet from 6 weeks of age until attaining a weight of ≥28 grams (6–8 weeks) to produce a fatty liver (histologically > 30% fat);steatosis was confirmed with lipidomic profile of liver tissue. Islets were infused via the intra-portal route in fatty-liver and control mice after streptozotocin induction of diabetes. Outcomes were assessed by the rate of euglycemia, liver histopathology, evaluation of liver inflammation by measuring tissue cytokines IL-1β and TNF-α by RT-PCR and CD31 expression by immunohistochemistry. Results: The difference in the euglycemic fraction between the normal liver group (90%, 9/10) and the fatty-liver group (37.5%, 3/8) was statistically significant at the 18 th day post- transplant and was maintained to the end of the study (day 28) (p = 0.019, X 2 = 5.51). Levels of TNF–α and IL-1β were elevated in fatty-liver mice (p = 0.042, p = 0.037). Compared to controls cytokine levels were elevated after islet cell transplantation and in transplanted fatty-liver mice as compared to either fatty- or islet transplant group alone (p = NS). A difference in the histochemical pattern of CD31 could not be determined. Conclusion: Fatty-liver creates an inflammatory state which adversely affects the outcome of autologous islet cell transplantation.